Syntactic Error Analysis in Writing Arabic Sentences at Tsanawiyah Level and Its Implications - Nabila Rahmafillah; Ari Khairurrijal Fahmi (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This study aims to identify writing errors in simple Arabic sentences made by students at the Tsanawiyah (Islamic junior high school) level. The research employs a qualitative approach using case study and content analysis methods. Data collection techniques include participatory observation, structured interviews, and document analysis. The data source consists of 45 sentences written by students in constructing jumlah ismiyah (nominal sentences). The findings show that out of the 45 collected simple sentences, 20 were identified to contain syntactic errors. Furthermore, based on the data and interview results, the causes of these errors were found to be both interlingual and intralingual. Interlingual errors occur when students mix rules from their native language with the target language, while intralingual errors result from confusion or lack of understanding of the target language itself. Students' difficulties in writing simple Arabic sentences, as revealed through interviews and error analysis, include a lack of awareness in selecting vocabulary that is perceived as correct but does not align with native speaker usage. In addition, challenges arise in choosing the correct gendered forms (masculine vs. feminine), number (singular, dual, plural), and determining the proper i'rab (grammatical case endings) and syntactic positions of words. This research may serve as a reference for understanding the level of difficulty students face in constructing simple Arabic sentences. It can also be used as a benchmark for evaluating teaching effectiveness and for enhancing the design of Arabic language learning strategies within educational institutions.